Implementation of Online Learning in The Pandemic Covid-19: Student Perception in Areas with Minimum Internet Access - Laksana, Dek Ngurah Laba (Journal of Education Technology, 2020)
The application of online learning was carried out massively during the Covid-19 pandemic. Its implementation certainly raises many new things, especially for areas with minimal internet access. For that, it is necessary to conduct a study of how students perceive online learning. The study was conducted to determine students’ perceptions of implementing online learning during the Covid-19 pandemic in minimal internet access areas. This type of research is a qualitative descriptive study, where the research subjects are students of a private university in East Nusa Tenggara, Indonesia. This research was conducted in four stages, namely (1) data collection, (2) data reduction, (3) data presentation, (4) concluding. The instrument used was a questionnaire consisting of 21 questions. Data analysis was carried out descriptively. The results showed that students had different perceptions of the administration of online lectures. These perceptions include perceptions of online learning infrastructure by 57%, online learning skills by 53%, perceptions of the quality of online academic interactions by 69%, benefits of online learning by 53%, obstacles faced by 42%, supporting factors for online learning by 38%, and future online learning expectations of 54%. This study concludes that students’ various online learning perceptions during the Covid-19 pandemic, starting from infrastructure, quality of interaction, and students’ benefits.